2013
DOI: 10.1007/s00167-013-2410-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of open wedge high tibial osteotomy on the lateral tibiofemoral compartment in sheep. Part II: standard and overcorrection do not cause articular cartilage degeneration

Abstract: Opening wedge HTO resulting in both standard and overcorrection is a safe procedure for the articular cartilage in an intact lateral tibiofemoral compartment of adult sheep at 6 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 60 publications
1
46
0
1
Order By: Relevance
“…Osteophytes always occurred in the periphery of the anterior and intermediate regions of the medial tibial plateaus, similar to other translational 23 , 31 and clinical studies 32 . Previously, the ovine tibial plateau has been divided into regions based on distinguishing the central and peripheral areas 21 ; meniscus covered and not covered regions 20 ; inner, middle, and outer thirds 22 ; cranial, middle and caudal thirds (each middle third was further divided into axial and abaxial aspects) 23 , 24 as well as grids containing 9 25 or 26 individual subregions 26 . Comparable regions were established on the human tibial plateau, for example by dividing it into meniscus covered and not-covered regions 33 , or in concentric zones (border and centre rings) 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteophytes always occurred in the periphery of the anterior and intermediate regions of the medial tibial plateaus, similar to other translational 23 , 31 and clinical studies 32 . Previously, the ovine tibial plateau has been divided into regions based on distinguishing the central and peripheral areas 21 ; meniscus covered and not covered regions 20 ; inner, middle, and outer thirds 22 ; cranial, middle and caudal thirds (each middle third was further divided into axial and abaxial aspects) 23 , 24 as well as grids containing 9 25 or 26 individual subregions 26 . Comparable regions were established on the human tibial plateau, for example by dividing it into meniscus covered and not-covered regions 33 , or in concentric zones (border and centre rings) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3-D image registration is available to aid with the problem of identical sample orientation 18 , 19 . So far, regions on the ovine tibial plateau were defined either visually (based on the presence of menisci 20 , separation into halves 21 or thirds 22 – 24 ), by mathematical modelling or using measured 25 or projected grids 26 . However, objectively definable and reproducible regions based on stable, easily identifiable reference points are largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…26 Areas containing OA changes were measured on digitalized photographs (analySIS 5.0; Olympus Soft Imaging System) within a standardized region of interest (width, 3.5-4.0 mm; area, 70 mm 2 ) surrounding the defect. 48 For histological and immunohistochemical evaluations, osteochondral specimens were trimmed and decalcified, and paraffin-embedded transversal sections (4 mm) were stained with safranin orange/fast green (safranin O) and hematoxylin and eosin according to routine protocols. 20 Defect areas were evaluated on a total of 130 histological sections taken from the center of the defects, applying the complex grading system according to Sellers et al 41 (31 points: no repair; 0 points: complete regeneration).…”
Section: Evaluation Of Cartilage Repairmentioning
confidence: 99%
“…Osteochondral defects provoked significantly more severe osteoarthritic degeneration of the adjacent cartilage than chondral lesions after 6 months in vivo. This time point was chosen based on the extensive experience with ovine cartilage repair after 6 months by several research groups 15,17,19,20,26,[44][45][46] and the suitability of this observation period to assess the development of osteoarthritis. 5 In accordance, Hepp et al 24 confirmed degenerative perilesional changes already 3 months after creation of cylindrical 7 mm osteochondral defects in ovine femoral condyles.…”
mentioning
confidence: 99%